2008
DOI: 10.1089/scd.2007.0102
|View full text |Cite
|
Sign up to set email alerts
|

Dlk1Influences Differentiation and Function ofβLymphocytes

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 50 publications
7
71
0
Order By: Relevance
“…On the other hand, activation of B cells during the recognition of thymusdependent antigens needs the cooperation of T cells activated earlier. In this sense, our previous work revealed that Dlk1-deficient mice showed an increased primary T-dependent antibody response [31]. These results are consistent with an improved antigen presentation by macrophages and dendritic cells from Dlk1-null animals, which can be due, at least in part, to a greater expression of co-stimulatory molecules and cytokines implicated in T-cell differentiation.…”
Section: Discussionsupporting
confidence: 81%
“…On the other hand, activation of B cells during the recognition of thymusdependent antigens needs the cooperation of T cells activated earlier. In this sense, our previous work revealed that Dlk1-deficient mice showed an increased primary T-dependent antibody response [31]. These results are consistent with an improved antigen presentation by macrophages and dendritic cells from Dlk1-null animals, which can be due, at least in part, to a greater expression of co-stimulatory molecules and cytokines implicated in T-cell differentiation.…”
Section: Discussionsupporting
confidence: 81%
“…As reported previously (24) and shown in Fig. 7A, Dlk1 2/2 embryos were smaller during development and postnatally (35).…”
Section: Loss Of Dlk1 Function Does Not Affect Bone Remodeling In Micesupporting
confidence: 88%
“…Dlk1-deficient (Dlk1 2/2 ) mice were obtained from J. Laborda (University of Castilla-La Mancha, Ciudad Real, Spain) (24). Osteoblast-specific Dlk1-overexpressing mice (expressing Dlk1 under collagen 3.6-kb promoter Col1-Dlk1) with high circulating levels of sDLK1 were generated by our group (13).…”
Section: Animalsmentioning
confidence: 99%
“…The Dlk1 (Delta-like 1 homologue) gene is expressed from the paternal allele. It encodes a protein with homology to members of the Notch-Delta family of signaling molecules, which is important for mammalian development (5)(6)(7). 80 kilobases downstream of Dlk1, the Gtl2 (gene trap locus 2) promoter is active only on the maternally inherited chromosome (8,9).…”
mentioning
confidence: 99%